Transtorno alimentar restritivo/evitativo em pacientes com doença inflamatória intestinal - Spiller, Amanda Luísa [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Inflammatory Bowel Disease (IBD) is a risk factor for Avoidant/Restrictive Food Intake Disorder (ARFID) due to dietary restrictions adopted during disease activity and often maintained during remission, impacting quality of life and body composition. This study aimed to evaluate the presence of ARFID and its impact on patients with IBD. A cross-sectional study was conducted with 122 patients, using the Nine Item Avoidant/Restrictive Food Intake Disorder Screen (NIAS) questionnaire, translated and validated for the Portuguese language to assess the presence of ARFID characteristics. The International Behavioral Questionnaire for Quality of Life (IBDQ) and the Food Frequency Questionnaire (FFQ) were also applied, along with anthropometric, bioimpedance, and muscle strength assessments. Of the participants, 28 (23%) presented ARFID characteristics, predominantly women (78.6%), with a mean age of 43.8 years. Patients with ARFID presented lower body mass index (23.45 kg/m²), smaller arm circumference (AC: 27.85 cm; p < 0.009) and calf circumference (CC: 33.45 cm; p = 0.02), as well as a smaller phase angle (5.78º; p <0.007). Significant negative correlations were observed between ARFID and albumin (r = –0.27; p = 0.003) and creatinine (r = –0.19; p = 0.04). Dietary intake assessed by the FFQ showed greater restriction of fruits, vegetables, and cheese (p ≤ 0.04). Patients with ARFID characteristics presented worse quality of life, with a significant reduction in the intestinal, systemic, social, and emotional domains of the IBDQ (p ≤ 0.01), and a higher risk of depression (p = 0.007). Multivariate analysis indicated that CP and phase angle are independent predictors of ARFID. It is concluded that the presence of ARFID characteristics in IBD patients is associated with restrictive eating patterns, poorer nutritional status, and reduced cellular integrity, as well as a negative impact on quality of life and increased depressive symptoms. These findings reinforce the need for integrated nutritional and psychosocial assessment in IBD patients.

A Doença Inflamatória Intestinal (DII) é um dos fatores de risco para o Transtorno Alimentar Restritivo/Evitativo (TARE), devido às restrições alimentares adotadas durante a atividade da doença e muitas vezes mantidas na remissão, impactando a qualidade de vida e a composição corporal. Este estudo teve como objetivo avaliar a presença de TARE e seu impacto em pacientes com DII. Realizou-se um estudo transversal com 122 pacientes, sendo traduzido e validado para a língua portuguesa o questionário Nine Item Avoidant/Restrictive Food Intake disorder screen (NIAS) para avaliação da presença de características do TARE, além da aplicação do Questionário de qualidade de vida (IBDQ) e questionário de frequência alimentar (QFA), realização de avaliações antropométricas, bioimpedância, força muscular. Dos participantes, 28 (23%) apresentaram características de TARE, predominantemente mulheres (78,6%), com idade média de 43,8 anos. Pacientes com TARE apresentaram menor índice de massa corporal (23,45 kg/m²), menor circunferência de braço (CB: 27,85 cm; p < 0,009) e panturrilha (CP: 33,45 cm; p = 0,02), além de menor ângulo de fase (5,78º; p <0,007). Correlações negativas significativas foram observadas entre TARE e albumina (r = –0,27; p = 0,003) e creatinina (r = –0,19; p = 0,04). A ingestão alimentar avaliada pelo QFA mostrou maior restrição de frutas, verduras e queijo (p ≤ 0,04). Pacientes com característica de TARE apresentaram pior qualidade de vida, com redução significativa nos domínios intestinal, sistêmico, social e emocional do IBDQ (p ≤ 0,01), e maior risco de depressão (p = 0,007). A análise multivariada indicou que a CP e ângulo de fase são preditores independentes de TARE. Conclui-se que a presença de características de TARE em pacientes com DII está associada a padrões alimentares restritivos, pior estado nutricional, e menor integridade celular, além de impacto negativo na qualidade de vida e aumento de sintomas depressivos. Estes achados reforçam a necessidade de avaliação nutricional e psicossocial integrada em pacientes com DII.
Transtorno alimentar restritivo/evitativo em pacientes com doença inflamatória intestinal
Keywords: Doença inflamatória intestinal; Crohn, Doença de; Proctocolite; Desnutrição; Transtorno alimentar restritivo/evitativo